Peningkatan Kompetensi Komunikasi Positif Orang Tua Anak Usia Dini melalui Penyuluhan Partisipatif - Ani Safitri; Umi Fatonah; Ria Maisalinia; Uccu nuryani (Journal of Community Empowerment, 2026)
This community service activity aims to improve parents' understanding and skills in implementing positive communication to build a sense of security and affection in early childhood. The activity was conducted at Nurul Hasanah Preschool, targeting parents of students. The implementation method used a participatory approach through the stages of needs identification, material planning, counseling, and evaluation. Techniques used included interactive lectures, brainstorming, and question-and-answer sessions. Initial identification results indicated that some parents still used high-pitched communication and had not optimally implemented active listening techniques. After the counseling, parents' understanding of the importance of empathetic communication, the use of positive language, and emotional management when interacting with children increased. Participants' enthusiasm was evident in the interactive discussion session. Although there were challenges such as a lack of focus due to the presence of children during the activity, the provision of an educational play area ensured the effectiveness of the activity. This program had a positive impact on parents' awareness of creating a safe emotional environment for children. Keywords: positive communication; participatory counseling; parental role; sense of security.